2021
DOI: 10.1007/s00249-021-01544-2
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of histidine 30 by asparagine in manganese superoxide dismutase alters biophysical properties and supports proliferation in a K562 leukemia cell line

Abstract: We have generated a mutant of C. elegans manganese superoxide dismutase at histidine 30 by site-directed mutagenesis. The structure was solved at a resolution of 1.52 Å by X-ray crystallography (pdb: 6S0D). His30 was targeted, as it forms as a gateway residue at the top of the solvent access funnel to the active site, together with Tyr34. In the wild-type protein, these gateway residues are involved in the hydrogen-bonding network providing the protons necessary for the catalytic reaction at the metal center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…In fact, HFEPR spectra of the wild-type S. aureus MnSOD and the mutants were different [40]. This is also in accordance with the findings of Bonetta et al where both metal specificity as well as the electronic structure of the C. elegans H30N MnSOD mutant were altered, despite not undergoing any changes in the backbone structure [25]. Barwinska-Sendra et al concluded that the altered metal specificity caused by the mutations is therefore, related to modified electronic structures and changes in the manganese reduction potential to become more catalytically active with iron [27].…”
Section: Metal Selectivity and Enzyme Activity In Mnsod Mutantssupporting
confidence: 91%
See 2 more Smart Citations
“…In fact, HFEPR spectra of the wild-type S. aureus MnSOD and the mutants were different [40]. This is also in accordance with the findings of Bonetta et al where both metal specificity as well as the electronic structure of the C. elegans H30N MnSOD mutant were altered, despite not undergoing any changes in the backbone structure [25]. Barwinska-Sendra et al concluded that the altered metal specificity caused by the mutations is therefore, related to modified electronic structures and changes in the manganese reduction potential to become more catalytically active with iron [27].…”
Section: Metal Selectivity and Enzyme Activity In Mnsod Mutantssupporting
confidence: 91%
“…The latter substitution retained only 50% of the enzyme activity and became cambialistic as it exhibited enzyme activity with either iron or manganese. The substitution of histidine 30 by asparagine in C. elegans MnSOD also lead to a reduction in the incorporation of manganese and an increase in iron [25]. Although the H30N mutant took up iron spontaneously in addition to manganese, enzyme activity was reduced to 22% compared with the wild-type (Figure 4).…”
Section: Metal Selectivity and Enzyme Activity In Mnsod Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Geographical extent of the ARBRE-MOBIEU network membership in 2020, at the end of its funding by COST publications with multiple network members listed as authors. In addition, this special issue of the European Biophysics Journal includes a diversity of original research articles, describing for instance the secondary structure analysis of CueR (Balogh et al 2021), the characterisation of the complex formed between Fep1 and DNA (Miele et al 2021) the analysis of the Dps-DNA interaction in Marinobacter hydrocarbonoclasticus (Jacinto et al 2021), the characterisation of melanoma cell markers (Sobiepanek et al 2021), the single-molecule study of cadherin bond rupture forces (VijiBabu et al 2021), the study of a sulphur iron protein (Almeida et al 2021) and that of a manganese superoxide dismutase variant (Bonetta et al 2021). These are good examples of how the network is helping research groups enhance their understanding of biological systems through an improved use of biophysical approaches.…”
Section: Scientific Outputs Of the Mobieu Cost Actionmentioning
confidence: 99%